Microstructure and tribological properties of Al2O3 reinforced FeCoNiCrMn high entropy alloy composite coatings by cold spray - Lupoi, Rocco (My University, 2022)
High entropy alloys (HEAs) are novel materials that have been extensively studied in recent years. In this work, Al2O3 particles reinforced FeCoNiCrMn HEA composite coatings were fabricated by cold spray. The microstructure, mechanical and tribological properties of the composites coating were studied and compared with those of the pure FeCoNiCrMn coating. The results indicate that cold spray is a promising process to fabricate HEA composite coatings. The composite coatings made in this work had higher hardness than pure FeCoNiCrMn coating due to the reinforcing effect of well distributed Al2O3 particles. The composite coatings also had improved wear-resistance properties with nearly 50% reduction in wear rate as compared to the pure FeCoNiCrMn coating. The improvement was due to the formation of tribo-layer which can effectively withstand material loss. The results also reveal that the main wear mechanisms for the composite coatings were dominated by adhesive wear in comparison to abrasive wear for the pure FeCoNiCrMn coating. This study proves the feasibility of cold spray for the fabrication of high-performance HEA composite coatings.
PUBLISHED
Keywords: High entropy alloys (HEAs); Al2O3 particles; Tribological properties; Mechanical properties; Microstructure; Composite coatings; High entropy alloys (HEAs); Cold spray (CS)